Two new species of Eugenia sect. Phyllocalyx (Myrtaceae) from Brazil - de Oliveira Bünger, Mariana; Mazine, Fiorella Fernanda; Stehmann, João Renato (Kew bulletin, 2018)
Two new endangered Brazilian species of Eugenia are described and illustrated, E. magnisepala and E. salacifolia. Eugenia magnisepala, collected in Matas de Cipó (liana forests) in the northeastern state of Bahia, recognisable by its larger calyx lobes, membranaceous blades and costate ovary, traits not shared with the morp hologically similar species E. itacarensis, E. involucrata, E. macrobracteolata and E. regia. Eugenia salacifolia was collected in seasonal Atlantic forests of the state of Minas Gerais and is similar to E. macrantha, from which it can be distinguished by its auxotelic inflorescences and larger and persistent bracteoles and calyx lobes.